Evaluation of flanking airborne sound transmission involving intensity and vibration measurement techniques for in situ conditions - Andrade, C.A.R. (2010)
Building structures can provide different flanking transmissions in situ condition compared to those in laboratory. Two different measurement techniques were used and compared for this paper. Both techniques measured the airborne sound insulation in buildings (between rooms) and evaluated the contribution of the partition wall and respective flanking walls. The Intensity measurement technique was used according to EN-15186-2. The Vibration measurement technique was used following some specifications of the EN-10848, this method is also evaluated as a procedure to be used instead of the Intensity technique. This paper reports the first results obtained by both techniques used in situ and estimates the overall flanking contribution for different types of junction in common Spanish buildings.